THE ROLE OF R & D AND OPEN INNOVATION ACTIVITIES ON INNOVATION PERFORMANCE; A CASE OF INDONESIA COMPANIES - Askawati Askawati (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2021)
R&D activities and implementation of open innovation in Indonesian companies are still very limited. Research related to the relationship between R&D activities and innovation performance based on the type of innovation and implementation of open innovation is only carried out in the manufacturing industry. Therefore, this study aims to develop previous research to see the effect of R&D activities and the implementation of open innovation on innovation performance in Indonesian companies, especially in the service and manufacturing sectors. Innovation performance is measured by the sales capacity of innovative products, both radical and incremental. The data used is the 2014 Indonesia Innovation Survey (IIS) for the period 2011-2013. The research data were processed using the Tobit regression method. The results found that internal R&D activity has a positive effect on the company's innovation performance both radically and incrementally. Indonesian companies are still lacking in collaborating with other partners because external R&D activities that are carried out both separately and simultaneously do not have an impact on innovation performance. In addition, the implementation of open innovation in Indonesian companies can have a radical influence on the company's innovation performance.